Research on an Improved Wireless Sensor Networks Clustering Protocol - Zheng-Qiu Lu; Lin-Ge Wang; Jin Shan (Institute of Advanced Engineering and Science, 2013)
Energy consumption of clustering routing protocol is one of the exigent problems needs to solve in wireless sensor networks. Aiming at the uneven energy consumption and unreasonable cluster heads selection in LEACH protocol, a new clustering routing protocol is proposed in this paper including number of cluster heads, cluster head choosing algorithm and network topology. Finally we give some analysis and comparison between the improved protocol and other two protocols, and the results show that the improved protocol can increase node energy-efficiency and prolong network survival lifetime. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3431